Respiratory Disorders in Rett Syndrome - Spoto, Giulia; Accetta, Arianna Santina; Grella, Maria; Di Modica, Irene; Nicotera, Antonio Gennaro (Current Respiratory Medicine Reviews, 2025)
Rett Syndrome (RTT) is a rare and severe neurodevelopmental disorder affecting children in the early stages of infancy and associated with a MECP2 mutation in 95-97% of individuals with typical RTT. Nearly all of the patients show breathing abnormalities during their lifespan, both in wake and sleep and respiratory illness represents an important cause of morbidity and mortality in RTT. Pathogenic mechanisms underlying breath-holding and other breathing abnormalities in RTT are mainly related to dysautonomia and an alteration in respiratory control at different levels, including several regions of the central and peripheral nervous system. Pathogenic variants in the MECP2 gene have been implicated in the dysfunction of respiratory pathways, affecting chemosensitivity and the response to neurotransmitters. In addition, frequent comorbidities such as scoliosis, dysphagia, sleep disorders, and epilepsy can further impair the respiratory function in these patients.
Keywords: Rett syndrome